Evaluation of Malassezia and Common Fungal Pathogens in Subtypes of Chronic Rhinosinusitis. Issue 9 (6th May 2016) - Gelber, Jonathan T.; Cope, Emily K.; Goldberg, Andrew N.; Pletcher, Steven D.
Abstract : Background: Fungal hypersensitivity and fungal microbiome dysbiosis are possible etiologies of chronic rhinosinusitis. The sinus fungal microbiome is not well characterized; novel sinus‐associated fungi, including Malassezia, have only recently been described. The goals for this study were to verify Malassezia as a dominant component of the sinus microbiome, to speciate sinus Malassezia, and to compare select fungal species in chronic rhinosinusitis (CRS) subtypes with known fungal association to chronic rhinosinusitis with polyps (CRSwNP) and healthy controls. Methods: Twenty‐eight patients were enrolled and categorized as CRSwNP (n = 15), fungus ball (n = 3), allergic fungal rhinosinusitis (AFRS, n = 3), or healthy control (n = 7). Brush samples were taken from ethmoid or maxillary sinus mucosa and tested for DNA from 7 index fungi using quantitative polymerase chain reaction. Index fungal species were chosen based on existing data of the sinus fungal microbiome. Results: Malassezia species were detected in 68% of patients, without variation among clinical phenotypes ( p > 0.99). Malassezia restricta was more commonly detected than Malassezia globosa ( p = 0.029). Presence of one Malassezia species predicted the presence of the other ( p = 0.035). Aspergillus was identified in 2 of 3 of fungus ball patients (both A. fumigatus ) and 2 of 3 AFRS patients (1 A. fumigatus and 1 A. flavus ). Aspergillus was absent in control and CRSwNP patients ( p < 0.001). Conclusion: This study confirmed and speciated Malassezia in healthy and diseased sinuses. Presence of Malassezia species in all groups suggests a commensal role for the fungus. Future work will determine whether Malassezia influences CRS pathogenesis. Aspergillus species were identified in fungal CRS subtypes despite negative surgical cultures, highlighting the importance of culture‐independent technology.